Relationship between push and pull motivation factors and intention to visit Muslim-friendly hospitals for medical tourism among Malaysian Muslims - Sobani, Rizq Nadiah (2023)
The Muslim-friendly medical tourism holds a great potential in assisting with the post-covid efforts for the country. As of current literature, there are no prior research on what drives Malaysian Muslim consumers to visit Muslim-friendly hospitals. This study proposes the effects of push and pull motivational factors on the intention to visit Muslim-friendly hospitals for medical tourism. A structured questionnaire was designed and distributed to 400 respondents who were sampled through multistage random sampling throughout the five zones in Malaysia: North Zone, East Zone, West Zone, South Zone and Borneo Zone. Multiple regression analysis was used to analyse the data in examining the relationship between the push factors (religiosity, electronic word-of-mouth, and novelty-seeking), pull factors (Islamic attributes, doctor practice, environment and safety, and tourism facilities) and the intention to visit Muslim-friendly hospitals for medical tourism. The result of the analysis denoted that religiosity, Islamic attributes, and environment and safety were the main push and pull factors that respectively predict the consumers intention to visit Muslim-friendly hospitals for medical tourism. Electronic word-of-mouth, novelty-seeking, doctor practice, and tourism facilities were however found to not able to predict the intention. This study can serve as a framework to enhance Malaysia’s Muslim-friendly hospitals to cater to medical tourists, both locally and internationally. The findings of this research can also contribute to the government and industry players in their post-covid efforts to revive local medical tourism industry and subsequently boost the Malaysian economy.